YouTube as a learning modality for clinical procedures among medical and dental students: a study in public sector teaching institutes - Hina Shah; Sanaa Ahmed; Sumbul Ayaz; Amna Gul; Urooj Fatima; Mohammad Taha Abbas (Journal of the Pakistan Medical Association)
Objectives: To evaluate the effectiveness and analyse the influence of YouTube as a learning modality for clinical procedures among medical and dental students in a public-sector setting.